Is the small size of a breast cancer tumor the crucial point for successful medical treatment? - Strunová, Marie; Pavlišta, David; Kobilková, Jitka; Pokorný, Jiří; Janoušek, Miloslav; Bauerová, Lenka; Jandová, Anna (Prague medical report, 2014)
The presented case displays a clinical study of a cancer phenotype with a poor clinical outcome. Prediction of cancer development and effects of treatment at the beginning of the clinical stage is difficult as the knowledge of cancer process and all necessary parameters of the host body are limited. Cancer is mainly studied on the basis of biochemical-genetic processes and their morphological manifestation. However, the malignant process is assumed to be of essential biophysical nature and develops after mitochondrial dysfunction, which is a direct result of oncogene mutation. Cancers based on the normal and the reverse Warburg effect should be distinguished. The cancer tumors with the reverse Warburg effect display aggressiveness associated with a high rate of recurrence and metastatic implantation. Besides the nature of the two basic types of breast cancer tumors the outcome depends not only on their type, size, and site but also on reactions and interaction with the surrounding tissue and the body aptitude for metastatic activity connected with individual blood or lymphatic vessels for metastatic transport. It is necessary to assess all favourable and adverse factors for cancer development. General reliable method of their specification for all cancers is not available. Nevertheless, the main factor seems to be aggressiveness of cancer cells as follows from interpretation. To reveal the aggressive reverse Warburg effect tumors, metabolic biomarkers of the fibroblast stress should be examined.
Keywords: Carcinoma, Ductal, Breast; duktální karcinom prsu; nádory prsu; Middle Aged; ženské pohlaví; prognóza; Breast Neoplasms; Humans; Tumor Burden; Female; tumor burden; Prognosis; lidé; lidé středního věku